Under pressure? Forced migration and public health - Renan Marques; Mateus Maciel; David Zuchowski (Global Labor Organization (GLO), 2026)
We study how Venezuelan refugee inflows affect healthcare outcomes and municipal public finances in Brazil's universal, decentralized public healthcare system. For identification, we exploit cross-municipality variation in refugee exposure and use distance to Brazil's only official border crossing with Venezuela as an instrument. A one-percentage-point increase in the local refugee share raises overall mortality by 4.2 percent and infant mortality by up to 9 percent. We show these effects operate through both the poorer baseline health of arriving refugees and congestion in local health facilities. Municipalities increase the share of spending on healthcare, but absent compensating federal transfers, they do so at the expense of education's budget share. These results highlight the limits of decentralized service provision in absorbing the health and fiscal costs of concentrated migration shocks.
Keywords: H75; J61; I10; 330; Forced migration; refugees; public health; Brazil